The Authority of Hadith in the Interpretation of the Al-Quran: A Study of Majlis Tarbiyah Garut Recitation - Yusuf Burhanuddin (al-Afkar, Journal For Islamic Studies, 2026)
This study presents field data on the thought of the Qur’aniyyun of the Majlis Tarbiyah Garut and offers an analysis of the relationship between the rejection of hadis authority and the construction of exegetical methodology within local study groups. The study not only analyzes the texts of Qur’aniyyun thought but also examines the practice of Qur’anic interpretation in study group activities firsthand. The doctrines they adhere to are: the Qur’an as the primary Holy Book; acceptance of the Sunah but rejection of hadith; interpretation of the Qur’an through the Qur’an itself; and the obligation to take the oath of allegiance (bay’at) and the testimony of faith (syahadat) in the presence of their leader.